A Mechanically Interlocking Strategy Based on Conductive Microbridges for Stretchable Electronics. Issue 7 (2nd January 2022) - Zhu, Ming; Ji, Shaobo; Luo, Yifei; Zhang, Feilong; Liu, Zhihua; Wang, Changxian; Lv, Zhisheng; Jiang, Ying; Wang, Ming; Cui, Zequn; Li, Guanglin; Jiang, Longtao; et al.
Abstract: Stretchable electronics incorporating critical sensing, data transmission, display and powering functionalities, is crucial to emerging wearable healthcare applications. To date, methods to achieve stretchability of individual functional devices have been extensively investigated. However, integration strategies of these stretchable devices to achieve all‐stretchable systems are still under exploration, in which the reliable stretchable interconnection is a key element. Here, solderless stretchable interconnections based on mechanically interlocking microbridges are developed to realize the assembly of individual stretchable devices onto soft patternable circuits toward multifunctional all‐stretchable platforms. This stretchable interconnection can effectively bridge interlayer conductivity with tight adhesion through both conductive microbridges and selectively distributed adhesive polymer. Consequently, enhanced stretchability up to a strain of 35% ( R / R 0  ≤ 5) is shown, compared with conventional solder‐assisted connections which lose electrical conduction at a strain of less than 5% ( R / R 0  ≈ 30). As a proof of concept, a self‐powered all‐stretchable data‐acquisition platform is fabricated by surface mounting a stretchable strain sensor and a supercapacitor onto a soft circuit through solderless interconnections. This solderless interconnecting strategy for surface‐mountable devices can be utilized as a valuable technology for the integration of stretchable devices to achieve all‐soft multifunctional systems. Abstract : Solderless stretchable interconnections (SLSIs) are developed to realize the assembly of individual soft devices toward multifunctional all‐stretchable integrated platforms. This stretchable interconnection can effectively bridge interlayer conductivity with tight adhesion through regional functionality. SLSIs show promising stretchability up to a strain of 35% ( R / R 0  ≤ 5) and can be adopted to achieve an all‐stretchable self‐powered data acquisition platform.